(untitled) (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the worlds, and blessings and peace be upon the most honorable messengers, our Prophet Muhammad . Pardon and forgiveness are one of the morals that a Muslim should have for peaceful coexistence, as it is one of the ways to strengthen social relations, and it is a set of good morals that bestow prestige and elegance on their owner. A tolerant person is loved by all people because he transcends mistakes and does not carry any grudge in his heart. Rather, he deals with the mistakes of others with the principle of good conjecture. The forgiving person possesses the hearts of others with love and forgiveness of slips, and we must acknowledge that the world around us suffers from a scarcity in tolerance and poverty in Peaceful coexistence. Based on this, the nature of the research required that it focuses on two topics, and every topic was in two demands: As for the first topic: it is about the definition of pardon and forgiveness and the statement of the related words and it was in two demands.The second topic is about the meaning of pardon and forgiveness in the Holly Quraan and their traces on the society and it is two demands. The conclusion was an explanation of the researcher’s most important findings. We ask Allah to benefit everyone by this study, and to make it achieve its goals, and praise be to Allah, Lord of the worlds, and blessings and peace be upon the master of Muhammad and his family and companions as a whole.